Re-imagining crisis care: experiences of delivering and receiving the Assured brief psychological intervention for people presenting to Emergency Departments with self-harm - Shah, Neha; O’Keeffe, Sally; Hayward, Sam; Suzuki, Mimi; McCabe, Rose (Frontiers in Psychiatry, 2024)
Background Risk of suicide is increased immediately following emergency department (ED) attendance for self-harm. Evidence suggests that brief psychological interventions delivered in EDs are effective for self-harm. The Assured intervention comprises an enhanced biopsychosocial assessment in the ED, collaborative safety planning and three rapid solution focused follow-up sessions. Aim We addressed the following research questions: What were ED mental health liaison practitioners’ and patients’ experiences of the Assured intervention? What were the barriers and facilitators? What might the mechanisms be for improving experiences and outcomes? Methods We conducted a feasibility study of the Assured intervention in four EDs in Southeast England. Semi-structured interviews were conducted with 13 practitioners and 27 patients. Interviews were transcribed, coded line-by-line in Nvivo and thematically analysed using an inductive approach. Inter-rater reliability was calculated with a kappa coefficient of 0.744.